2022
DOI: 10.1007/s40121-022-00619-7
|View full text |Cite
|
Sign up to set email alerts
|

Late cART Initiation Consistently Driven by Late HIV Presentation: A Multicenter Retrospective Cohort Study in Taiwan from 2009 to 2019

Abstract: Introduction Late initiation (LI) of combination antiretroviral therapy (cART)—defined as having a CD4 + count of < 200 cells/μL or an AIDS-defining disease at cART initiation—has detrimental outcomes but remains prevalent worldwide, with LI trends and etiologies following the implementation of various HIV policies remaining underinvestigated. We assessed key concerns, characterized the determinants of various statuses at cART initiation, and evaluated the effects of tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 53 publications
1
7
1
Order By: Relevance
“…First, the slowing of the decline in all-cause mortality among MSM, MSW, WSM in our study population may be partly explained by the persistently high prevalence of late HIV presentation among those with sexually transmitted HIV in Taiwan over the past 2 decades 34 , 35 . This high prevalence, which contributes to AIDS-related deaths 30 , 36 , may partially nullify the benefits conferred by the reduction of mortality from improved medical care, the implementation of universal ART, and the introduction of a single-tablet regimen.…”
Section: Discussionmentioning
confidence: 90%
“…First, the slowing of the decline in all-cause mortality among MSM, MSW, WSM in our study population may be partly explained by the persistently high prevalence of late HIV presentation among those with sexually transmitted HIV in Taiwan over the past 2 decades 34 , 35 . This high prevalence, which contributes to AIDS-related deaths 30 , 36 , may partially nullify the benefits conferred by the reduction of mortality from improved medical care, the implementation of universal ART, and the introduction of a single-tablet regimen.…”
Section: Discussionmentioning
confidence: 90%
“…There are three outcomes used in this study. The first one is "late ART initiation," which was defined as having a CD4 cell count <200 cells/µL or having a clinical AIDS diagnosis at ART initiation (including having current clinical syndromes, opportunistic infections 3 months before ART initiation or at WHO stage III or IV), a definition used in four studies in China [14][15][16][17]. The second one is "delayed ART initiation," which provided an alternate measure of timely ART initiation based on self-reported HIV diagnosis date, and is defined as having a period of more than 1 month between HIV diagnosis date and ART initiation, a definition used in two national studies in China [5,18].…”
Section: Definition Of Late Art Initiation and Delayed Art Initiationmentioning
confidence: 99%
“…Previous studies have rarely compared different outcomes. In China, gender, transmission routes, age, and year of ART initiation were associated with late ART initiation [14][15][16], and marital status was found to be associated with delayed ART initiation [5]. Before 2016, the situation of ART initiation in China has been improving despite the challenges of inactive ART initiation remained [5].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, several studies reported no change or an increasing trend in late-initiating patients, reflecting challenges in implementing the ‘‘treat-all’’ scheme. Lee et al 41 noted a significant decrease in late ART initiation from 77.14% in 2009 to 39.1% in 2019, with a slight increase from 2015 to 2019 (33.03% to 37.80%). In Brazil, Pacheco et al 12 observed an increase from 2014 to 2018 despite a decreasing trend in previous years.…”
Section: Discussionmentioning
confidence: 99%